BOOSTING ESP STUDENTS’ LEARNING MOTIVATION THROUGH GEN-Z TEACHERS’ TECHNOLOGY INTEGRATION - Mudra, Heri (LLT Journal: A Journal on Language and Language Teaching, 2025)
The integration of technology in teaching ESP courses in rural universities has shifted from a conventional to an integrated learning process. Hence, technology integration remains challenging for urban Gen-Z teachers due to rural students' learning habits. This current study focused on how ESP teachers empowered technology to encourage rural students' positive learning emotions. Nine teachers with urban culture and habits from three rural universities were involved in the interview study. Based on deductive content analysis, the findings revealed students' preferences towards the types of learning technology (i.e., web-based apps, social media platforms, and electronic tools). Particular strategies (i.e., mobile learning and social media use, flipped classrooms, blogging, and podcasting) were indulged during the ESP course. On the other side, the teachers were challenged with teaching and learning barriers (i.e., linguistic, cultural and psychological) that reduced technology use quality. Above all, ESP courses in rural contexts should be promoted using a particular instructional design and approach.